Peran Literasi Digital Pada Mata Pelajaran Ips Materi Keragaman Alam Indonesia Dalam Mengembangkan Kemampuan Berpikir Kritis Siswa Kelas VIII Smp Negeri 9 Semarang - Fendi Alviansyach; Sanita Carolina Sasea (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2026)
This study aims to analyze digital literacy's role in developing 8th-grade critical thinking at SMP N 9 Semarang, focusing on Social Studies (IPS) subject, specifically on the Indonesian Natural Diversity material. A qualitative descriptive method was used, with data from teacher interviews, observations, and documentation analyzed using Piaget's constructivist theory. Results show digital literacy implementation is a planned pedagogical strategy. The issue-rich Indonesian Natural Diversity material triggered cognitive conflict. The teacher's role as a mediator in source evaluation was key to facilitating schema accommodation. It is concluded that digital literacy, supported by constructivist pedagogy, effectively transforms students from passive consumers into active critical knowledge constructors. Teachers are advised to design learning that consciously triggers students' cognitive conflict.